Caffeine Molecular Target Identification and Protein Interaction Analysis in Alzheimer's Disease - Fatriani, Rizka; Haryandi, Yopi; Khairani, Iffa Afiqa; Anisa, Hida Arliani Nur (MAXIMUS: Journal of Biological and Life Sciences, 2025)
Caffeine is known to have various biological effects, including its potential to modulate the central nervous system. This study aims to identify the molecular targets of caffeine and explore their relationship with Alzheimer's disease using a bioinformatics approach. The methods used include target prediction using SwissTargetPrediction and SuperPred, target relationship analysis with disease through the DAVID database, protein interaction exploration and enrichment analysis using STRING-DB, and network analysis using Cytoscape. The results showed that from the total targets obtained, there were 20 overlapping targets related to Alzheimer's. Protein interaction analysis revealed 17 nodes with 32 significant interactions, which provide insight into the molecular pathways that caffeine can manipulate in the context of neuroprotection. These findings are in line with various studies showing that caffeine consumption is associated with a reduced risk of Alzheimer's through modulation of the nervous system and inflammation.